An Autopsy Study of Pattern of Unnatural Deaths among Youth Conducted at a tertiary Care Teaching Hospital in South India - Narayankar, P M; Jagannatha, S R (Journal of Indian Academy of Forensic Medicine, 2023)
Mortality among youth owing to unnatural causes is on the rise. Hence, the present study was undertaken to assess the number of such  deaths, the manner of death and the commonest cause of death. Atotal of 255 cases of unnatural deaths among youth aged between 15 and  29 years, autopsied at a tertiary care teaching hospital in South India were studied for duration of 18 months from November 2015 to April  th 2017. Unnatural deaths among youth constituted 25.91%, 1/4 of all medico-legal autopsies. Males outnumbered females. Most of the  victims were 24 to 26 years old males and 21 to 23 years old females. Most of the victims were Hindu. Socio-economically, most of the  victims belonged to the middle class. Most of them were urban residents belonging to nuclear families. Majority of the victims were  secondary school students. Most of the unnatural deaths were suicides; with victims aged 27 to 29 years. In conclusion, most of the  unnatural deaths among youth were suicidal in nature followed by accidents and lastly homicides.
Keywords: Youth; Attempted suicide; Head injury; Traffic accidents; Homicides; Autopsies